ANALISIS SEMIOTIKA TIPOGRAFI PADA KEMASAN KONDOM DUREX INVISIBLE: VISIBLE ATAU INVISIBLE (?) - RIhi, Samuel (UNIVERSITAS NUSA PUTRA, 2024)
This text seeks to explore the complexities of typography and its intersections with gender and sexuality as seen in the typography on the packaging of Durex INVISIBLE condoms, using several semiotic typography analysis features offered by Theo van Leeuwen. The curvature feature distinguishes the use of rounded and angular shapes at every character corner, which symbolically represent masculinity and femininity, and illustrate the sexual pleasure that can be experienced by both women and men. The rounded text on the word